2022
DOI: 10.4235/agmr.22.0057
|View full text |Cite
|
Sign up to set email alerts
|

Calf Circumference Measurement Protocols for Sarcopenia Screening: Differences in Agreement, Convergent Validity and Diagnostic Performance

Abstract: Calf circumference measurement protocols for sarcopenia screening: Differences in agreement, convergent validity and diagnostic performance Melissa Rose Berlin Piodena-Aportadera a) , Sabrina Lau a),b) , Justin Chew a),b) Jun Pei Lim a),b) , Noor Hafizah Ismail b),c) , Yew Yoong Ding a),b) , Wee Shiong Lim a),b) a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…With some studies finding the significant influence of posture on CC measurement 21 , 22 , standardization is needed to ensure the reliability of CC as the screening indicator for possible sarcopenia. For instance, since some studies found that CC measurement in a standing position has higher accuracy and lower overestimation 21 , 23 , we need to consider standardizing the CC measurement in a standing position.…”
Section: Discussionmentioning
confidence: 99%
“…With some studies finding the significant influence of posture on CC measurement 21 , 22 , standardization is needed to ensure the reliability of CC as the screening indicator for possible sarcopenia. For instance, since some studies found that CC measurement in a standing position has higher accuracy and lower overestimation 21 , 23 , we need to consider standardizing the CC measurement in a standing position.…”
Section: Discussionmentioning
confidence: 99%
“…Anthropometric measurements were recorded, including height, weight, body mass index (BMI), mid upper arm circumference, calf circumference, and waist circumference. Calf circumference was measured using non‐elastic tape at the widest part of the dominant calf in the seated position with the weight evenly distributed on both feet 20 . MAC was measured at the mid‐point between the acromial surface of the scapula and the olecranon process of the elbow over the dominant arm when bent at 90°.…”
Section: Methodsmentioning
confidence: 99%
“…Calf circumference was measured using non-elastic tape at the widest part of the dominant calf in the seated position with the weight evenly distributed on both feet. 20 MAC was measured at the midpoint between the acromial surface of the scapula and the olecranon process of the elbow over the dominant arm when bent at 90 . Waist circumference was measured using measuring tape 2.5 cm above the umbilicus in standing position.…”
Section: Data Collectionmentioning
confidence: 99%
“…[7,[53][54][55] Additionally, questionnaires such as strength, assistance with walking, rising from a chair, climbing stairs, and falls (SARC-F) and ring tests using the thumb and index finger to measure calf circumference are suggested. [10,56] Notably, SARC-F has limitations as a screening tool due to its low sensitivity and high specificity. [57] Consequently, case identification in clinical practices may heavily rely on clinical suspicion, considering factors such as significant weight loss, general weakness, or history of falls, regardless of age.…”
Section: Screening Testmentioning
confidence: 99%